Slow motion ethics: Narrative responsibility in clinical care. (March 2022) - Pullman, Daryl
Narrative theory is a dynamic and evolving field of inquiry that has made tremendous inroads in the medical humanities over the past 40 years. Numerous authors have popularized the idea that "thinking narratively" can produce important insights about the illness experience for physician and patient alike. This paper draws on aspects of narrative theory to emphasize the moral responsibilities that arise when we step into another person's life narrative, becoming a character in her or his story. This has especially significant ethical implications for the physician–patient encounter in that each character in this shared story experiences time somewhat differently. This gives rise to the notion of "slow motion ethics" and a somewhat unique perspective on the moral responsibilities clinicians bear toward their patients.